Hubungan Indeks Massa Tubuh dengan Hipertensi pada Penderita Penyakit Ginjal Kronik di RSUD dr. Moewardi Surakarta - Anggrah, Yundari Suciningtyas, Dr. Suryo Aribowo Taroeno, M.Kes., Sp.P.D. (KHOM) (2017)
Background: Chronic Kidney Disease (CKD) is a disease with diverse etiology that lead progressively decrease a renal function, and sometimes can be a kidney failure. Kidney failure is a clinical condition characterized by an irreversible decrease renal function which in some levels require a medical or therapy fixed, like dialysis and kidney transplantation. The research from Persatuan Nefrologi Indonesia (PERNEFRI) also estimate that 70.000 patients with Chronic Kidney Disease can be found in Indonesia. Goals: To investigate relationship between body mass index and hypertension in patient with chronic kidney disease. Method: This study used analytic observational research with cross sectional approach. Subjects in this study amounted to 56 patients with chronic kidney disease which not undergone hemodialysis yet. The instrument used the medical record to seen body mass index and blood preassure. Results: The hypothesis was analyzed using Chi Square Test, which the statistical results is p=0,00, significance of p<0,05. It means H0 was rejected and H1 was accepted. Conclussion: There was a significant relationship between body mass index and hypertension in patient with chronic kidney disease.